Možnosti za ponovno uporabo odpadnega stekla - Ducman, Vilma (Kovine zlitine tehnologije, 1998)
The contribution is concerned with foamed-glass insulation boards, foamed granules and sintered mosaic glass nased on waste glass. Foamed glass samples were made by adding a foaming agent to powdered glass, and firing this mixture in moulds at temperatures within certain ranges above the glass softening point. Foamed granules were produced in a similar way. When powdered waste glass was pressed in moulds (together with a binder and pigments) and fired at temperatures above the softening point, sintered mosaic glass was obtained. The apparent density of foamed glass obtained in this way lies between 0.2 and 0.8 g/?$cm^3$?, and its microstructure is homogeneous, with pore sizes up to 3 mm, and compressive strength lies between 1 and 16 MPa. The values for the bending strength of the sintered mosaic glass tiles are greater than 40 MPa, their Moh's hardness is 6, and their water absorption is 0%. These tiles are also frost resistant.
Keywords: steklo; steklena vlakna; izolacijski materiali; penjenje; sintranje